Community-Based Marine Ecotourism Management in Prajak Area, Sumbawa - Fahrunnisa; Yuni Yolanda; Nurul Amri Komarudin (International Journal of Geotourism Science and Development, 2022)
Prajak is crowned as the top 300 tourist villages at the 2022 Indonesian tourism village award. Prajak is a hamlet located in the Saleh Bay cluster, Sumbawa, so development in this area is directed as a marine tourism area. Even though it is named a tourist village, the tourism conditions in Prajak are still not optimal and have not been developed properly. The condition of the beach is still natural, but the lack of public awareness of tourism opportunities and the inadequate infrastructure of existing tourism infrastructure have resulted in marine tourism in prajak is not yet known by the public. In addition, the main problem is the rampant illegal fishing which has an impact on the destruction of coral reefs, the reduction of fishermen's catches, and the threat to fish sustainability. Therefore, the development of non-extractive, non-consumptive, and sustainable natural resources needs to be prioritized in the field of tourism so that marine ecotourism is the main choice. This study aims to design an appropriate marine ecotourism zoning in Prajak Sumbawa area based on its ecological potential, analyze the feasibility of community-based marine ecotourism, and create a community-based marine ecotourism management strategy in Prajak, Sumbawa Regency.